RETRACTED: Icariin Ameliorates Palmitate-Induced Insulin Resistance Through Reducing Thioredoxin-Interacting Protein (TXNIP) and Suppressing ER Stress in C2C12 Myotubes - Li, Mingxin; Zhang, Yemin; Cao, Yingkang; Zhang, Deling; Liu, Le; Guo, Yanghongyun; Wang, Changhua (Frontiers in Pharmacology, 2018)
Both thioredoxin-interacting protein (TXNIP) and endoplasmic reticulum (ER) stress are implicated in skeletal muscle insulin resistance. Icariin has been found to mimic insulin action in normal skeletal muscle C2C12 cells and display anti-diabetic properties in diet-induced obese (DIO) mice. However, the underlying molecular mechanism remains to be well established. Herein, we tested the hypothesis that the protective effects of icariin on free fatty acid-induced insulin resistance were attributed to its regulation on TXNIP protein levels and ER stress in skeletal muscle cells. We found that TXNIP mediated the saturated fatty acid palmitate (PA)-induced insulin resistance in C2C12 myotubes. Icariin treatment significantly restored PA-reduced proteasome activity resulting in reduction of TXNIP protein and suppression of ER stress, as well as improvement of insulin sensitivity. Proteasome inhibition by its specific inhibitor MG132 obviously abolished the inhibitory effect of icariin on PA-induced insulin resistance. In addition, MG132 supplementation markedly abrogated the impacts of icariin on ER stress and TXNIP-mediated downstream events such as inflammation and STAT3 phosphorylation. These results clearly indicate that icariin improves PA-induced skeletal muscle insulin resistance through a proteasome-dependent mechanism, by which icariin downregulats TXNIP levels and inhibits ER stress.